2017
DOI: 10.1097/bot.0000000000000841
|View full text |Cite
|
Sign up to set email alerts
|

A Teachable Moment After Orthopaedic Fracture in the Smoking Patient: A Randomized, Controlled Trial

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Furthermore, it is important to consider that within the behaviours included in the analysis, the models, or certain model constructs, might be more relevant to particular behaviours. For example, the TM model was developed in the context of smoking cessation and is therefore frequently used to understand this behaviour, above others (Baron et al, 2017 ; McBride et al, 2003 ; McBride, Blocklin, Lipkus, Klein, & Brandon 2017 ). Furthermore, the ability of the COM-B model to explain behaviour has been suggested to vary across behavioural contexts; in particular, it has been found to better explain physical activity than it has eating behaviour (Willmott, Pang, & Rundle-Thiele, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is important to consider that within the behaviours included in the analysis, the models, or certain model constructs, might be more relevant to particular behaviours. For example, the TM model was developed in the context of smoking cessation and is therefore frequently used to understand this behaviour, above others (Baron et al, 2017 ; McBride et al, 2003 ; McBride, Blocklin, Lipkus, Klein, & Brandon 2017 ). Furthermore, the ability of the COM-B model to explain behaviour has been suggested to vary across behavioural contexts; in particular, it has been found to better explain physical activity than it has eating behaviour (Willmott, Pang, & Rundle-Thiele, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that trauma represents a "teachable moment" which can be used to help influence behavior. 23,24,29 Orthopaedic patients require multiple interactions with the health care system, providing several opportunities to affect change. Simple education seems to be sufficient producing a short-term effect in smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the link between an injury and the willingness to quit smoking requires further exploration. The time of injury may represent an opportunity for attitudinal change and associated with a shift in the valuation of habits and well-being [59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%